A Systemic Review on the Management Approaches in Non-Specific Orbital Inflammation (Journal of National Institute of Ophthalmology, 2026)
Background: Non-Specific Orbital Inflammation (NSOI) or Idiopathic Orbital Inflammation (IOI) or orbital pseudotumor is an uncommon, non-systemic, non-infectious, and non-neoplastic inflammatory disorder of the orbit with a broad spectrum of clinical features. Despite being the third most common orbital disease, its diagnosis and treatment are unreliable because no standardized protocols exist. This systematic review critically evaluates and consolidates current diagnostic methods and treatment plans for IOI to facilitate evidence-based clinical decision-making. Methodology: Systematic PubMed and Google Scholar searches were conducted to identify English-language, open-access studies. The PRISMA protocol was followed to select studies. Seventeen studies were included in the final analysis. Result: NSOI is diagnosed through clinical assessment, MRI or CT imaging, and selective biopsy. Systemic corticosteroids is first-line therapy, achieving >80% initial response but with 29–37% recurrence and frequent steroid-dependence. Steroid-sparing agents (methotrexate, azathioprine, mycophenolate) reduce relapse, while biologics (infliximab, rituximab) are effective in refractory cases. Radiotherapy serves as salvage for resistant disease, and surgery is mainly diagnostic or for selected structural indications. Prognosis depends on treatment timing and early response, with multidisciplinary care improving diagnostic accuracy and long-term outcomes. Conclusion: NSOI requires immediate diagnosis, tailored treatment, and multidisciplinary care to maximize results. Corticosteroids are the foundation, but immunosuppressants or biologics can be needed. Uniform diagnostic criteria and prospective studies are needed to optimize management algorithms and maximize long-term disease control.J.Natl.Inst.Ophthalmol.2024;7(2): 76-83